2020
DOI: 10.22540/jfsf-05-079
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of sarcopenia among patients underwent abdominal CT scan in Tertiary Care Hospital of South India

Abstract: The term sarcopenia is derived from the Greek meaning 'poverty of flesh' and is characterized by the progressive loss of skeletal muscle mass, muscle strength, and physical performance. This term was first coined by I.H. Rosenberg to denote "ageing related loss of skeletal muscle mass and strength" 1. Sarcopenia has a biological component with the genes involved in skeletal muscle mitochondrial function, oxidative capacity, and glucose uptake showing reduced expression with ageing 2. It affects women and men e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…An Indian hospital‐based study published in 2020 which looked at computerized tomogram assessment of sarcopenia showed men were eight times more likely to be sarcopenic than women. 21 Similar findings were reported from a Chinese community study (19.2% men vs 8.6% women). 22 Possible reasons include the rapid decline in muscle mass due to age‐dependent reduction in testosterone and insulin‐like growth factor‐1 levels in men.…”
Section: Discussionsupporting
confidence: 85%
“…An Indian hospital‐based study published in 2020 which looked at computerized tomogram assessment of sarcopenia showed men were eight times more likely to be sarcopenic than women. 21 Similar findings were reported from a Chinese community study (19.2% men vs 8.6% women). 22 Possible reasons include the rapid decline in muscle mass due to age‐dependent reduction in testosterone and insulin‐like growth factor‐1 levels in men.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Iannuzzi-Sucich et al who assessed sarcopenia by BIA and clinical testing in a healthy older population, found men to be sarcopenic 4% more often than women, a discrepancy which increased in the age cohort of those over 80 years 42 . Similarly, higher rates of sarcopenic male patients have been described in some CT based body composition studies 43 , 44 . However, it should be noted that contradictory study results with a slightly higher sarcopenia prevalence among women have also been published 45 and that the patient number of this study’s collective was limited.…”
Section: Discussionmentioning
confidence: 56%
“…In a multicontinental study involving a healthy elderly population, 17.5% of Indians had sarcopenia, a considerably higher figure than other Asian countries and Europe [ 17 ]. Similarly, a hospital-based study from South India reported a sarcopenia prevalence of 54% among older adults who underwent imaging for non-malignant indications [ 18 ].…”
Section: Discussionmentioning
confidence: 99%